Increased interleukin-26 in the peripheral joints of patients with axial spondyloarthritis and psoriatic arthritis, co-localizing with CD68-positive synoviocytes - Hammitzsch, Ariane; Ossadnik, Andreas; Bachmann, Quirin; Merwald-Fraenk, Helga; Lorenz, Georg; Witt, Matthias; Wiesent, Franziska; Mühlhofer, Heinrich; Simone, Davide; Bowness, Paul; Heemann, Uwe; Arbogast, Martin; et al. (Frontiers in Immunology, 2024)
Objectives: IL-26 levels are elevated in blood and synovial fluid of patients with in-flammatory arthritis. IL-26 can be produced by Th17 cells and locally within joints by tissue-resident cells. IL-26 induces osteoblast mineralization in vitro. As osteoprolif-eration and Th17 cells are important factors in the pathogenesis of axial Spondyloar-thritis (axSpA), we aimed to clarify the cellular sources of IL-26 in Spondyloarthritis. Methods: Serum, peripheral blood mononuclear cells (n=15-35) and synovial tissue (n=3; 7-9) of adult patients with axSpA, Psoriatric Arthritis (PsA), Rheumatoid Arthritis (RA) and Healthy Controls (HC, n=5) were evaluated by ELISA, Flow Cytometry in-cluding PrimeFlow Assay, Immunohistochemistry and -fluorescence, and quantitative PCR. Results: Synovial tissue of axSpA shows significantly more IL-26 positive cells than of HC (p<0.01), but numbers are also elevated in PsA and RA. Immunofluorescence shows colocalization of IL-26 with CD68, but not CD3, SMA, CD163, Cadherin-11 or CD90. IL-26 is elevated in the serum of RA and PsA (but not axSpA) patients com-pared to HC (p<0.001 and p<0.01). However, peripheral blood CD4+ T cells from axSpA and PsA patients show higher positivity for IL26 in the PrimeFlow Assay com-pared to HC. CD4+ memory T cells from axSpA produce more IL-26 under Th17-favouring conditions (IL-1 and IL-23) than cells from PsA, RA or HC. Conclusion: IL-26 production is increased in the synovial tissue of SpA and can be localized to CD68+ Macrophage-like synoviocytes, whilst circulating IL26+Th17 cells are only modestly enriched. Considering the osteoproliferative properties of IL-26, this offers new therapeutic options independent of Th17 pathways.